Isolation, phylogeny and characterization of proteases and p-hydroxyphenylacetic acid hydroxylase from thermophilic Geobacillus strains from Buranga Hot Springs in Uganda - Brözel, Volker Siegfried (University of Pretoria, 2013)
Thesis (PhD (Microbiology))--University of Pretoria, 2003.